Analysis of difficulties in solving mathematical problems categorized higher order thinking skills (HOTS) on the subject of rank and shape of the root according to polya stages - Ernawati; Sutiarso, S (Journal of physics. Conference series, 2020)
Destination of this research is to identify difficulties faced by the students in solving mathematical problems HOTS categorized on the subject of rank and shape of the root. This research was classified as descriptive research with a qualitative oncoming. In this study, researc subjects numbered 115 students, after going through data reduction, the data focused on 4 students representing high, medium, and low abilities, to precede the process of looking deeper into the process of working on problems based on Polya's stages. Data collection techniques in this study were observation, tests, and interview. In this study, the authors used persistence observation techniques and data triangulation. Based the results and discussion of study showed so as 62.54% of students had difficulty understanding the problem, 70.62% of students had difficulty thinking of a plan, 79.68% of students had difficulty implementing the plan, and 87.16% of students had difficulty reviewing. Difficulty factors in solving mathematical problems categorized HOTS on the theory of rank and shape of the root is students do not understand what is called a problem, students aren't able absorb information properly, weaknesses prerequisite concepts owned by the student, the student aren't careful and thorough the process, lack experience students working on math problems categorized HOTS, and lack student experience in working on story problems.